Female Directors and Carbon Information Disclosure: Evidence from China - Ren He; Mingdian Zhou; Jing Liu; Qing Yang (Discrete Dynamics in Nature and Society)
In recent years, natural disasters and public health events caused by global warming have occurred frequently around the world. It has become a global consensus to actively respond to climate change. Firms are the main source of greenhouse gas emissions. The disclosure of carbon information is one of the most important ways for firms to respond to climate change. The effect of female directors on carbon information disclosure is still unclear. Considering that China is the largest country in greenhouse gas emissions and the social status of females in China is different from western countries, this paper explores the effect of female directors on carbon information disclosure by firms in China. Based on the sample of listed Chinese firms in high carbon industries during the period of 2012–2017, our empirical results show that female directors have a positive association with carbon information disclosure. In addition, we find that the power, educational level, and financial background of female directors have positive impacts on firms’ carbon information disclosure. Our findings make a significant contribution to the ongoing debate on the role of female directors and provide new insights and policy implications for firms, regulators, and other stakeholders.